Perawatan Komprehensif Geligi Campuran pada Anak Usia 8 Tahun dengan Riwayat Ibu memiliki Celah Bibir – Laporan Kasus - Anisa Nursantika; Jeffrey Jeffrey (Denta Journal Kedokteran Gigi, 2020)
Cleft lip and palate are abnormal clefts in the orofacial region that affect lip, alveolar bone, hard palate, and or soft palate. An eight-year-old girl came to Dental Hospital of Unjani with her mother, with chief complaint tooth cavity on the left and right of the lower arch and want to be treated. Intraoral findings found that the patient’s teeth are crowded with a narrow jaw arch. From the anamnesis, the mother of the patient had a cleft lip and extend to the alveolar bone, but the patient itself has no cleft lip and palate. The comprehensive treatments that done to the patient are amalgam restoration of tooth 75 and pulp capping of tooth 85 with stainless steel crown as follow up restoration.